Every other day stereotactic radiation therapy for the treatment of uveal melanoma decreases toxicity. (November 2022) - Yazici, Gozde; Kiratli, Hayyam; Ozyigit, Gokhan; Sari, Sezin Yuce; Elmali, Aysenur; Yilmaz, Melek Tugce; Koc, Irem; Deliktas, Ozge; Gumeler, Ekim; Cengiz, Mustafa; Zorlu, Faruk
Highlights: After a median 74-month follow-up, the overall LC rate was 83% in UM treated with SRS/FSRT. A dose of ≥45 Gy and BED10Gy ≥112.5 yielded higher LRFS and EFS rates. Every other day treatment approach decreases the rates of toxicity and enucleation. Abstract: Background and purpose: To report the long-term results of stereotactic radiosurgery and fractionated stereotactic radiation therapy (SRS/FSRT) in patients with uveal melanoma (UM). Materials and methods: We retrospectively evaluated the results of patients treated between 2007 and 2019. The primary endpoints were local control (LC), local recurrence-free survival (LRFS), enucleation-free survival (EFS) and treatment toxicity. Results: 443 patients with 445 UMs were treated via CyberKnife®. According to the COMS classification, 70% of the tumors were small/medium and 30% were large. Median total RT dose was 54 Gy, median BED10 was 151 Gy. After a median 74-months follow-up, SRS/FSRT yielded an 83% overall LC rate. The 5- and 10-year LRFS rate was 74% and 56%, respectively. Patient age and the COMS size were prognostic for all survival endpoints. An increased SRS/FSRT dose was associated with higher LRFS and EFS rates. SRS/FSRT-related toxicity was observed in 49% of the eyes. Median visual acuity (VA) significantly deteriorated after SRS/FSRT in 76% of the treated eyes. The overall eye preservation rate was 62%, and the 5- and 10-year EFS rate was 64% and 36%, respectively. The delivery of FSRT every other day resulted in a significantly lower rate of toxicity and enucleation compared to FSRT on consecutive days. Conclusion: A total dose of ≥45 Gy and BED10Gy ≥ 112.5 SRS/FSRT is associated with a higher LC rate in patients with UM. Despite the favorable outcomes, treatment toxicity is the major limitation of this treatment. Toxicity and enucleation can be minimized by treating the eye every other day.